Ensuring budgetary resources at the level of local communities in the current social-economic context: Evidence for Romanian municipalities - Mihaela Onofrei; Ionel Bostan; Elena Cigu; Anca Florentina Gavriluta (Economies, 2023)
This paper aims to examine whether the status of fiscal decentralization generates efficiency in local spending behavior and leads to local fiscal performance and local economic growth, revealing not only the status of Romania from the point of vertical fiscal imbalance but also the fiscal implication of spending decentralization and local government effectiveness. The methodological background includes qualitative sequential methodology, involving empiric analysis that provides coherence and viability for our study, but also quantitative methods, including Ordinary Least Squares regression (OLS). The empirical results show that fiscal decentralization determines more responsible and efficient local spending, enhancing local performance and contributing to economic growth. Furthermore, the analysis provides evidence on the importance of local fiscal consolidation and gives an overview in terms of spending responsibilities between the central government and local government. The paper contributes to the literature that studies fiscal imbalance, as well as the fiscal implications of decentralized spending and the effectiveness of local governments in driving economic growth. It also contributes to the literature that studies the relationship between fiscal decentralization and local economic growth, as well as the effectiveness of government reforms and strategies.
Keywords: 330; budgetary resources; current social-economic context; fiscal decentralization; fiscal imbalances; local communities; spending efficiency